Interpreting the prevalence of musculoskeletal pain impacting Italian and Peruvian dentists likewise: A cross-sectional study - Macrì, Monica; Flores, Natali V. Galindo; Stefanelli, Riccardo; Pegreffi, Francesco; Festa, Felice (Frontiers in Public Health, 2023)
Background Musculoskeletal pain is a frequent condition among dental practitioners due to working in prolonged static isometric/eccentric contraction. The study aimed to describe musculoskeletal pain prevalence and the interplay between environmental conditions, lifestyle, and drugs consumed among Italian and Peruvian dentists. Methods A 18 multiple choice questionnaire was administered to Peruvian and Italian dental care practitioners. A total of 187 questionnaires were submitted. 167 questionnaires were selected for the analysis, including 86 questionnaires from Italy, 86 were submitted from Italy and 81 from Perú. The study examined musculoskeletal pain presence in dental practitioners. The prevalence of musculoskeletal pain presence was analysed considering different parameters: gender, age, type of dental practitioners, specialisation in dentistry, hours of work per day, years of work, physical activity, localisation of musculoskeletal pain and the influence of musculoskeletal pain on the performance on work. Results The selected questionnaires for analysis were 167 (67 from Italy and 81 from Perú). Male and female participants were numerically equal. Most of the dental practitioners were dentists. The percentage of dentists who present musculoskeletal pain is 87,2% in Italy and 91,4% in Perú (p0,05). Conclusion Musculoskeletal pain represents a very diffused condition in dental practitioners. The results about the prevalence of musculoskeletal pain show how the two populations (Italian and Peruvian) are very similar despite the geographical distance. Nevertheless, the high percentages of musculoskeletal pain in dental practitioners translate into the need to use solutions to reduce its onsets, such as improving ergonomics and physical activity.